Dwell in Possibility: PLAR and e-Portfolios in the Age of Information and Communication Technologies - Brown, Judith O. (International Review of Research in Open and Distributed Learning, 2011)
Emily Dickinson wrote, “I dwell in Possibility—A fairer House than Prose—More Numerous of Windows—Superior—for Doors” (p. 657). Dickinson’s simple yet profound reference to the expansive nature of poetry over prose may be taken as a metaphor for the possibilities of information and communication technologies (ICTs) over written modes of expression. Whether we identify with this analogy or not, what we can say today with some certainty is that the advent of ICTs has impacted prior learning assessment and recognition (PLAR) by expanding the potential for knowledge acquisition, expression, and delivery. The purpose of this article is to examine the potential of experiential learning e-portfolios to promote connections between several different types of learning – academic, workplace, and web-based. The author contends that this type of PLAR enables undergraduate adult learners to not only articulate and equate experiential learning to academic knowledge but also, and most importantly, to demonstrate knowledge visually and audibly through the utilization of ICTs. Two pilot case studies of e-portfolio development are described to support the author’s position.